A good sine? Seeking math help using crowdsourced online discussion boards. (January 2020) - Kim, Ann Y; Thacker, Ian
We examined asynchronous online discussion boards, specifically those that are unmediated by teacher figures, to identify characteristics of these spaces that support or constrain students as they seek help in mathematics. We analyzed 86 questions and 114 associated responses posted to two Khan Academy discussion boards centered around two related trigonometry lessons. The platform created a space where students could ask a variety of questions ranging from those requesting math definitions and explanations of math procedures to justifications for why formulas are true. However, crowdsourced replies to questions were delayed, sometimes taking more than one year for a reply to be posted; content of student replies did not always match the content of the questions posed; and the quality of the replies varied considerably, some replies were helpful or resourceful while others were incorrect or vague. These challenges seemed connected to the unmediated nature of this type of asynchronous online discussion board. We argue that this online learning environment demands additional self-regulated learning strategies such as awareness of one's needs and the timeframe in which they must be met. We also discuss implications for research and practice.